2022
DOI: 10.3386/w30430
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Female Teachers on Female Students' Lifetime Well-Being

Abstract: It is widely believed that female students benefit from being taught by female teachers, particularly when those teachers serve as counter-stereotypical role models. We study education in rural areas of the US circa 1940--a setting in which there were few professional female exemplars other than teachers--and find that female students were more successful when their primary-school teachers were disproportionately female. Impacts are lifelong: female students taught by female teachers were more likely to move u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
3
4
0
Order By: Relevance
“…The findings of this study, which highlight a positive relationship between female teachers and schooling outcomes, align with earlier research conducted by Card et al (2022), Wahsheh & Alhawamdeh (2015), Kirk (2006), Rugh (2000), Banerjee et al (2000), and Herz et al (1991) regarding the impact of female teachers in education. The positive and statistically significant relationship between female teachers and education outcomes provides a strong message that female teachers can help to improve education outcomes in developing countries through various ways.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of this study, which highlight a positive relationship between female teachers and schooling outcomes, align with earlier research conducted by Card et al (2022), Wahsheh & Alhawamdeh (2015), Kirk (2006), Rugh (2000), Banerjee et al (2000), and Herz et al (1991) regarding the impact of female teachers in education. The positive and statistically significant relationship between female teachers and education outcomes provides a strong message that female teachers can help to improve education outcomes in developing countries through various ways.…”
Section: Discussionsupporting
confidence: 91%
“…Female Teachers as a percentage of total teachers of a particular level is taken as a control variable because female teachers may advocate more in society regarding the importance of education and the future benefits of literacy. In addition, female teachers provide a conducive classroom environment and facilitate other educational activities (Card et al, 2022;Kirk, 2006;Wahsheh et al, 2015).…”
Section: Data and Variables Selectionmentioning
confidence: 99%
“…We note that our research design does not allow us to provide a process explanation for the observed interaction effect. Nonetheless, we speculate that female entrepreneurs with higher aspirations are more attuned to female role models which, in turn, helps them overcome the sticky stereotypes and gender-specific roles of entrepreneurs in developing countries (e.g., Card et al 2022), thereby reinforcing their self-efficacy.…”
Section: Heterogeneous Effects: Does Aspiration Matter?mentioning
confidence: 90%
“…In addition, female teachers provide a conducive classroom environment and facilitate other educational activities. Earlier research conducted by Card et al (2022), Kirk (2006), and Wahsheh & Alhawamdeh (2015) highlighted a positive relationship between female teachers and schooling outcomes. Similarly, the World Bank (2001b), Herz et al (1991), Rugh (2000), and Banerjee et al (2000) emphasized hiring female teachers to increase girls' enrolment.…”
Section: Data and Variables Selectionmentioning
confidence: 94%